Multiple submucosal lipomas of small intestine: a case report - Tiwari, Kritika; Raghuvanshi, Rhishikesh J.; Athale, Anuja; Deshpande, Suresh G. (International Surgery Journal, 2020)
Small bowel obstruction can be due to benign or malignant pathologies. Gastro intestinal lipomas are one of the benign subepithelial tumours causing obstruction. These are usually detected incidentally if asymptomatic. Adult intussusception due to intestinal lipoma is a very rare cause. We are presenting a case of male hypertensive patient with features of multiple subacute obstruction due to multiple submucosal lipomas in ileum. Exploratory laparotomy with intra-operative enteroscopy was performed and resection-anastomosis of affected segment was done.